Effect of Temperature on Nutrient Removal Efficiency of Water Hyacinth for Phytoremediation Treatment - Haris, Harizah; Fai, Chow Ming; Bahruddin, Ainun Shakirah Binti; Dinesh, Akhilash Aravind A L (International Journal of Engineering and Technology, 2018)
Wetlands have been introduced as natural based devices for treating the stormwater runoff.Â Temperature plays an important role in the nutrient removal process of wetland plants. Thus, the effect of temperature on nutrient removal efficiency of the water hyacinth plant was evaluated in this study. Water quality of both tanks that containing water hyacinth plants and control tank were monitored continuously for 2 weeks. The collected water samples were examined for total phosphorous (TP), turbidity, dissolved oxygen (DO), pH, conductivity (Cond.), total dissolve solid (TDS) and water temperature. The results showed that there are changes in the water quality concentration although there is no water hyacinth in the control tank. The release of phosphorus from the organic matter and particle in the control tank is suggested that occurred during the high temperature period. The optimum removal of nutrient occurred during the water temperature at 30â„ƒ. This clearly showed the effect of temperature on the flux of phosphorus in the water tank.